Emo Demo vs Lecture: A Comparative Study of Counseling Methods on Mothers' Attitudes Toward Stunting In Porong Public Health Center - Aqilah Rahma Pritana Widiyanto; Ani Intiyati; Mujayanto; Inne Soesanti (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Stunting is a chronic nutritional issue that adversely affects children's growth and development, and remains a significant public health challenge in Indonesia, including in the Porong Health Center area, Sidoarjo. This study aimed to compare the effectiveness of two counseling methods—Emo Demo and lectures—on improving the attitudes of mothers with stunted children under five. A pre-experimental design with one-group pretest–posttest was used, involving 20 respondents who were divided evenly into two groups. Each group received nutrition counseling using either the Emo Demo or lecture method. Data were analyzed using the Paired Sample T-Test and the Independent T-Test/Mann-Whitney to measure changes and compare attitudes before and after the intervention. The results showed a significant improvement in maternal attitudes within both groups: Emo Demo (p = 0.001) and lecture (p = 0.045). However, there was no statistically significant difference between the two methods (p = 0.121). Despite this, the average increase in attitude scores was higher in the Emo Demo group (27%) compared to the lecture group (13%). These findings suggest that while both methods are effective in improving attitudes toward balanced nutrition, the Emo Demo method may offer greater practical impact in supporting behavior change among mothers.